DISKURS OF SIMULACRA IN KOVACEVIĆ’S DRAMA BALKAN SPY - Milojević, Snežana J. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
This paper is based on a reading of the famous Dušan Kovačević’s drama Balkan Spy, contextualized by postulates of simulacra. The starting point for finding symbols that corresponded to the system of the non-referent world (and each such system creates its own reality, and proceeds from its own frame in which it must be interpreted) is a book of Jean Baudrillard “Simulacrum and Simulation”. Through chapters that accentuate simulacrum-like phenomena for proving the actual through imaginary and cloned, as well as defining the world of literary text as a kind of Disneyland, it becomes evident soundness of this idea that confirms the quality of this drama.